Pengaruh Disiplin Kerja dan Insentif terhadap Kinerja Karyawan pada PT Sun Star Prima Motor Dealer Mitsubishi Siliwangi - Aldy Afrizal Setiawan; Aprilia Puspasari (Journal of Islamic Economics and Finance, 2025)
This study aims to determine the influence of work discipline and incentives on employee performance at PT Sun Star Prima Motor Dealer Mitsubishi Siliwangi. The background of this research is based on the importance of internal factors such as discipline and incentivization in encouraging increased work productivity in the automotive sector, especially in the motor vehicle dealer environment. The research method used was quantitative with an associative approach, where data was collected through questionnaires distributed to 53 respondents who were permanent employees in the operational and administrative departments. The data analysis technique uses multiple linear regression to test the extent to which the variables of work discipline (X₁) and incentives (X₂) affect employee performance (Y). The results of the study show that work discipline has a significant positive effect on employee performance and the incentives provided, proven to have a significant and positive influence on performance improvement. Simultaneously, the two independent variables made a significant contribution to improving employee performance with a calculated f-value of 33.695 which means > f the table or 33.695 > 3.187 and a significance value of 0.000 which is smaller than 0.05 or 0.000 < 0.05. The conclusion of this study is that managerial efforts in improving work discipline and providing appropriate incentives can be an effective strategy in encouraging employee performance in the automotive dealer sector.